Legal protection of landscape in the process of land development. Selected issues - Świderski, Krzysztof (Przegląd Prawa Rolnego, 2021)
Landscape is an element of the earth’s surface. The aim of the considerations is to answer the question if and to what extent the legislator subjects landscape to protection in the process of land development, whether this protection covers only the natural shape of the terrain or whether it also includes the possibility of its improvement. In conclusion, the author states, among other things, that the formation of the land affects the usable and natural values of the earth’s surface. However, changes to the shape of the terrain made appropriately to its intended use are not forbidden, provided that the principles of sound land management are observed. It is not the legislator’s intention to preserve the natural landform unconditionally. What matters is also its foreseen utility and values. Therefore, transformation of landforms may be permitted on condition that it is beneficial, increases the utility of the land and does not adversely affect any of the adjacent land or the environment.